2011
DOI: 10.1017/s1751731110001540
|View full text |Cite
|
Sign up to set email alerts
|

Leptin in farm animals: where are we and where can we go?

Abstract: Fat affects meat quality, value and production efficiency as well as providing energy reserves for pregnancy and lactation in farm livestock. Leptin, the adipocyte product of the obese (ob) gene, was quickly seen as a predictor of body fat content in animals approaching slaughter and an aid to assessing reproductive readiness in females. Its participation in inflammation and immune responses that help animals survive infection and trauma has clear additional relevance to meat and milk production. Furthermore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 318 publications
(263 reference statements)
0
33
1
2
Order By: Relevance
“…Leptin concentration increases during pubertal development in heifers [30] and in sheep [8], and leptin has been proposed to signal that the critical thresholds for body fat mass have been reached and thus are considered permissive for onset of puberty [10,31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin concentration increases during pubertal development in heifers [30] and in sheep [8], and leptin has been proposed to signal that the critical thresholds for body fat mass have been reached and thus are considered permissive for onset of puberty [10,31].…”
Section: Discussionmentioning
confidence: 99%
“…Control of age at onset of puberty is known to be influenced by genetics, with moderate heritability [6,7]. Factors such as body weight, growth, and body fat are important regulators of age at onset of puberty [8][9][10][11]. Because sheep are seasonal breeders, measuring age at onset of puberty can be complex, and we have recently observed that the proportion of ewe lambs that failed to attain puberty before 1 yr of age (i.e., during their first breeding season) varied from 9% to 35%, while the average age of those ewes that did attain puberty remained relatively constant (approximately 8 mo).…”
Section: Introductionmentioning
confidence: 99%
“…It has been postulated that leptin acts as a permissive signal to the occurrence of puberty (Wylie, 2010). Therefore, insuffi cient nutrient availability or depleted body reserves followed by depressed plasma leptin would attenuate the ability of other signals to trigger puberty or even act as an absolute gating mechanism for puberty (Cunningham et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecular markers associated with characteristics of economic interest are the genes, among which we can mention: DGAT1 (diacylglycerol acyltransferase 1), a gene that encodes the enzyme of the same name acting in the metabolism of intestinal fat absorption, lipoprotein synthesis, adipose tissue formation, and lactation (Nonneman and Rohrer, 2002;Cui et al, 2011); LEP (leptin) and LEPR (leptin receptor) are important regulators of appetite, metabolism, reproduction (Wylie, 2011;Georgescu et al, 2014), and the deposition of intramuscular fat ); H-FABP (heart-type fatty acid binding protein) is related to the regulation of fatty acid uptake and intracellular transport (Gerbens et al, 1999;Chao et al, 2012); MC4R (melanocortin 4 receptor gene) is an important genetic marker for characteristics related to backfat thickness, feed intake, and growth rate (Jokubka et al, 2006;Óvilo et al, 2006); SREBF1 (sterol regulatory element binding transcription factor) involved in the differentiation of adipocytes, as well as cholesterol and fatty acids (Stachowiak et al, 2013); and GH (growth hormone) that influences economically important characteristics such as carcass weight and fat thickness (Franco et al, 2003;Bižienė et al, 2011).…”
Section: Introductionmentioning
confidence: 99%